2020
DOI: 10.1088/1742-6596/1567/4/042088
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of mobile learning role play game (rpg) maker mv in improving students’ critical thinking ability

Abstract: The aim of this research were to improve students’ critical thinking and to know students’ responses in applying mobile learning RPG-based maker MV in Ecosystem learning. This research is experimental research by using quasi-experimental design with Randomized control-Group Pretest Posttest. The data was taken qualitatively by using observation results during students’ learning, students’ response questionnaire in experiencing mobile learning RPG based maker MV, and quantitative data of students’ critical thin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 3 publications
1
5
0
2
Order By: Relevance
“…Dalam dunia pendidikan, siswa perlu mengembangkan kemampuan berpikir kritisnya agar dapat menggunakan pemikirannya secara kritis untuk memecahkan masalah tertentu (Kane et al, 2016). Menurut (Rasyid et al, 2020) dan Noer (2009), berpikir kritis adalah proses yang mengarah pada kesimpulan tentang apa yang harus kita yakini dan apa yang kita lakukan. Ia tidak hanya mencari jawaban, tetapi lebih dari itu menanyakan pertanyaan tentang jawaban, fakta, atau informasi yang ada.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Dalam dunia pendidikan, siswa perlu mengembangkan kemampuan berpikir kritisnya agar dapat menggunakan pemikirannya secara kritis untuk memecahkan masalah tertentu (Kane et al, 2016). Menurut (Rasyid et al, 2020) dan Noer (2009), berpikir kritis adalah proses yang mengarah pada kesimpulan tentang apa yang harus kita yakini dan apa yang kita lakukan. Ia tidak hanya mencari jawaban, tetapi lebih dari itu menanyakan pertanyaan tentang jawaban, fakta, atau informasi yang ada.…”
Section: Pendahuluanunclassified
“…Menurut (Rasyid., et al 2020) dan Setyawati (2013), ciri-ciri orang yang memiliki kemampuan berpikir kritis adalah memecahkan masalah untuk tujuan tertentu, menganalisis dan menggeneralisasi ide berdasarkan fakta yang ada, menarik kesimpulan, dan memecahkan masalah secara sistematis, yaitu kemampuan memecahkan masalah. Dengan diskusi yang tepat.…”
Section: Pendahuluanunclassified
“…This approach is mainly based on a combination of hand-on classes, classroom discussions, online discussions, interactive simulators, and various assessment forms that involve and instruct students, as well as ensure a productive asynchronous interaction with the teacher [ 9 ]. It is shown that critical thinking, as well as academic performance, can be improved by using educational games such as Role Play Games [ 10 ]. Currently, mobile software is considered progressive in terms of developing critical thinking skills.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the synthesis of the results underscores the transformative role of innovative teaching methods like gamification and blended learning in fostering critical thinking. Borglum [ 9 ] and Rasyid et al [ 10 ] illustrate how educational games and blended learning approaches, respectively, significantly facilitate the development of critical thinking skills. These methods, which combine traditional and digital pedagogical techniques, engage students more effectively, as well as provide diverse platforms for them to apply critical thinking.…”
Section: Introductionmentioning
confidence: 99%
“…We use this media to improve motivation and learning outcomes of coastal students. Charta Media has many advantages such as easy to make, inexpensive, simple, practical, and can be used for all levels of teaching and fields of study (Rasyid et al, 2020). The selection of environmental waste such as mineral water bottles and pipette rods is our effort to stimulate coastal students' thinking about the use of environmental waste as an alternative solution to the low availability of learning media.…”
Section: Introductionmentioning
confidence: 99%